INFLUENCE OF TIKTOK MARKETING ON URBAN YOUTH BRAND LOYALTY IN PENANG, MALAYSIA - Lim, Lay Ai; Chee, How Liau (INTI International University, 2023)
Social media trends are part of today’s society where these technologies can reach out globally to the consumers which play vital digital marketing campaign role for the companies to create the tendency of continuing buying from them than other competing companies. Statistics show that there is an increasing trend of using social media marketing by the marketers that consider the platform is low cost and can be used to compete in the market. The research aimed to investigate the popular social media which is TikTok about its marketing activities’ impacts on the urban youth’s brand loyalty among the Malaysia’s state of Penang. TikTok application is one of the fastest growing social media platforms and the short video app is popular among younger generation of users as well. Social media marketing approaches such as entertainment, trendiness, and electronic word of mouth (eWOM) are used in this study to explore the only dependent variable which is brand loyalty. Data is collected through online questionnaire from the youth respondents that have TikTok user account through a snowballing sampling and total of 113 responses were received. Using SPSS software, the data is analyzed to validate measurements and test the hypothesis. Demographic profile analysis, factor analysis, pilot testing, validity and reliability test, statistical analysis and regression analysis are presented in the table forms. The findings and results of this study show that entertainment marketing content and eWOM have significant influence on brand loyalty. Conversely, trendiness TikTok marketing activities do not attract Penang youth’s brand loyalty. This study may academically contribute to the companies that use TikTok platform to determine the dominant factors that influence the consumers’ loyalty on their brands.